Mobility and session management UMTS vs. cdma2000. - Ai-Chun Pang (IEEE Wireless communications)
This article describes the mobility and session management mechanisms for UMTS and cdma2000 packet-switched (PS) service domains, and compares the design guidelines for these two third-generation technologies. We first introduce the network architectures and protocols for UMTS and cdma2000, and then elaborate on the PS service domain's mobility management, session management, and IP-level mobility mechanisms. Based on the mobility and session management mechanisms of the UMTS and cdma2000 PS service domains, an integrated architecture and intersystem roaming procedures are proposed to show the implementation feasibility of UMTS-cdma2000 IP-level interworking.